The "Mobile You" breathalyzer - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
The X275 Mobile You Breathalyzer is a portable, handheld breathalyzer device made by Youtoi Industries of Japan. Following successful marketing of the product in Japan, the company is expanding its focus to Germany. This case study presents a comparison of the Japanese and German markets and asks readers to consider how Youtoi should conduct its market research and whether it will be as successful in Germany as in Japan.